2016
DOI: 10.7717/peerj.2558
|View full text |Cite
|
Sign up to set email alerts
|

Effect of orthodontic debonding and residual adhesive removal on 3D enamel microroughness

Abstract: BackgroundTermination of fixed orthodontic treatment is associated with bracket debonding and residual adhesive removal. These procedures increase enamel roughness to a degree that should depend on the tool used. Enamel roughening may be associated with bacterial retention and staining. However, a very limited data exists on the alteration of 3D enamel roughness resulting from the use of different tools for orthodontic clean-up.Aims1. To perform a precise assessment of 3D enamel surface roughness resulting fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 37 publications
1
19
0
7
Order By: Relevance
“…This can lead to an increased enamel loss of up to 60 lm with a tungsten carbide bur. 6 Enamel scratches should be avoided as much as possible 26 since they enhance bacterial adhesion 5 and cannot be eliminated by polishing. 27,28 These enamel alterations of bracket debonding and adhesive removal affect the optical properties of the enamel surface.…”
Section: Discussionmentioning
confidence: 99%
“…This can lead to an increased enamel loss of up to 60 lm with a tungsten carbide bur. 6 Enamel scratches should be avoided as much as possible 26 since they enhance bacterial adhesion 5 and cannot be eliminated by polishing. 27,28 These enamel alterations of bracket debonding and adhesive removal affect the optical properties of the enamel surface.…”
Section: Discussionmentioning
confidence: 99%
“…There are studies that have used confocal microscopy and atomic force microscopy, which analyze a smaller area than that assessed in the present study. 25 26 …”
Section: Discussionmentioning
confidence: 99%
“…While this finding is in agreement with the fact that the 37% PA etchant yields the highest bond strengths in comparison to any other etchant, this unnecessarily excessive bond strength has been a point of contention as it is frequently accompanied by varying forms of enamel damage (8,24). In addition, since the debonding inevitably leaves adhesive remnants on the enamel surface, enamel clean-up and polishing is required to remove these remnants (usually using rotary burs) resulting in increased chair-side time and enamel scratching (3,7). On the other hand, although enamel etching with SEP exhibited lower SBS (15.1-22.4 MPa) than the PA gel (23.4-29.8 MPa) at both bracket debonding time points, the values obtained were well above the minimum requirement for clinical performance (6-10 MPa).…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that an etch-and-rinse (EaR) approach using phosphoric acid remains the preferred choice for enamel conditioning in orthodontics since it guarantees a durable bracket bond to enamel (1,2). However, high shear bond strength (SBS) values have been accompanied by more adhesive residues with iatrogenic enamel fracture, chipping, or cracking due to the higher debonding force required to remove the brackets after treatment (3). Attempts to employ various concentrations of other acids such as pyruvic, lactic, nitric, maleic, tannic and citric acids resulted in suboptimal bond strengths not suitable for clinical performance and failed to outperform the etching ability of phosphoric acid (4).…”
Section: Introductionmentioning
confidence: 99%